LEKSIKON NAMA PENYAKIT DAN PENGOBATAN TRADISIONAL DALAM BAHASA MELAYU DIALEK PONTIANAK DI KECAMATAN KUBU - Aisyah, Nur; Saman, Sisilya; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractLexicon is the name of the disease presented well. Otherwise lexicon is the name of the disease and the traditional medicine in malay language Pontianak dialect in this study, we can see from the lexicon form, the meaning of lexicon, and from the lexicon is the name of disease and the traditional medicine produced suplement from text the leaming of Indonesian language curriculum 2013 revision from 2017. The results of this study used informal technique. Based on this study, the researcher was succesfull colect 84 lexicon the name of disease and the traditional medicine in Malay language Pontianak Diatect In Kubu district. From all of the data, obtained from the interview and the recording process. Lexicon the name of disease and the traditional medicine in this study consist of 2 from lexicons that is monomorphemic (single word) of 46 lexicon and polymorphims (denved words) of 38 lexicons. Lexicon name of disease and the traditional medicine as a whole has the meaning of lexical and meaning of cultural name of disease as much 24 lexicons and produced supplement from the learning of indonesian language curriculum 2013 revision from 2017.Keywords: Â Lexicon, Name of Disease, Malay Traditional Medicine, Semantic, Thematic Supplements of Indonesian Language Learning Text.Â